The Air Stability of Sodium Layered Oxide NaTMO2 (100) Surface Investigated via DFT Calculations - Hui Li; Qing Xue; Shengyi Li; Xuechun Wang; Yijie Hou; Chang Sun; Cun Wang; Guozheng Sheng; Peng Sheng; Huitao Bai; Li Xu; Yumin Qian (Nanomaterials)
Air stability caused by the H2O/CO2 reaction at the layered oxide NaTMO2 surface is one of the main obstacles to commercializing sodium-ion batteries (SIBS). The H2O and CO2 adsorption properties on the (100) surface of sodium layered transition metal oxide NaTMO2 (TM = Co, Ni, Mo, Nd) are calculated using the DFT method to study the surface air stability. This study showed that the material bulk phase (symmetry), surface site, element type, and surface termination are all (though not the only) important factors that affect the adsorption strength. Contrary to previous studies, the P phase is not always more air-stable than the O phase; our calculations showed that the NaNiO2 O phase is more stable than the P phase. The calculated band center and occupation showed a direct relationship with the adsorption energy. The Na site adsorption for CO2 and H2O showed the same V-shape trend. However, the TM adsorption for CO2 and H2O showed a different trend. With an increased t2g band center, CO2 adsorption strength increases. There is no clear trend for H2O adsorption. Our calculations showed that the electronic structure of the surface atomic of adsorption site plays a decisive role in CO2 and H2O adsorption strength. This study demonstrated an effective method for obtaining a stability parameter regarding the electronic structure, which can be used to screen the air-stable layered oxide sodium cathode in the future.